Epicocconone–Hemicyanine Hybrids: Near Infrared Fluorophores for Protein Staining and Cell Imaging. Issue 8 (15th December 2016) - Karuso, Peter; Loa Kum Cheung, Wendy; Peixoto, Philippe A.; Boulangé, Agathe; Franck, Xavier
Abstract: The development of new near infrared (NIR) dyes is crucial for diverse applications and especially bioimaging, as they absorb and emit light in the "therapeutic window" (650–950 nm). We report here a new family of NIR fluorophores that has been obtained by hybridising hemicyanines with epicocconone. Emission wavelengths of these hybrid dyes is in the range 715–795 nm and is combined with large Stokes' shifts (75–95 nm). The absorption and emission wavelength can be modulated according to the hemicyanine moiety and adding sulfonic acid moieties enhances water solubility. We demonstrate their application in the sensitive detection of proteins in gel electrophoresis and the staining of specific cellular organelles in confocal microscopy. These results are particularly encouraging and bring forward a new fluorescent skeleton for chemical biology. Abstract : The dye is cast : By hybridising hemicyanins and epicocconone, a new family of NIR fluorophores were obtained with emission wavelengths in the range 715–795 nm combined with large Stokes' shifts (75–95 nm). Their application in proteomic gel staining and confocal microscopy is demonstrated.